MEMBANGUN CITRA MERK YANG POSITIF PADA WISATA BUKIT TEGAL SANTUN - Sugiyanto Sugiyanto; Heri Prabowo; Henry Casandra Gultom; Bayu Kurniawan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service is carried out to introduce the brand that has been owned by Bukit Tegal Santun to the wider community. This PKM service activity uses a participatory community empowerment approach or Participatory Rural Appraisal (PRA), which is an in-process approach method. From the activities that have been carried out, the activity participants, namely the managers of Bukit Tegal Santun understand the importance of a brand, namely that a brand is able to distinguish the types of services and services provided by competitors. With a brand that is increasingly known to the wider community, it is hoped that it will increase tourists to Bukit Tegal Santun.